Fractional Factorial Design and Desirability Function-Based Approach in Spice Paprika Processing Technology to Improve Extractable Colour Stability - Arnold Koncsek; Lajos Szokol; Vivien Krizsa; Hussein G. Daood; Lajos Helyes; Antal Véha; Balázs Szabó P. (Polish Journal of Food and Nutrition Sciences)
The storage-stability of extractable colour in paprika powder is strongly influenced by the processing steps. The purpose of this research work was to decrease the degradation rate of extractable colour of paprika powders to 3-4 ASTA units/month and increase the shelf-life. Fractional factorial experimental design and desirability function-based approach was applied to moderate the adverse effect of the key-importance processing steps on colour agent content. Photochemical-accelerated shelf-life test was used for the empirically-based quality improvement. Post-harvest ripening, drying, sorting (seed content), milling and additives (paprika seed oil, tocopherol extract) were identified as important for the degradation rate of extractable colour. The colour stability was very sensitive to the milling and drying intensity, while proper setup of other processing steps compensated the adverse effect of drying and milling parameters. The supplementation with cold-pressed spice paprika seed oil was demonstrated as a natural way of colour stabilization. At the highest desirability value (0.986) the rate constant of accelerated colour stability test (k) and shelf-life time (θS[100ASTA]) were −0.494 ASTA units/day and 2326 days, respectively. Alternative factor level settings enabled taking into account processing-tradition and efficiency expectation. In these cases, desirability values and the predicted shelf-life were 0.5-0.8 and 712-918 days, respectively. Validation study showed that the real observed rate constant and shelf-life values met the predicted values and their 95% confidence interval.